Live-cell localization microscopy with a fluorogenic and self-blinking tetrazine probe - Werther, Philipp; Yserentant, Klaus; Braun, Felix; Baalmann, Mathis; Wombacher, Richard (Angewandte Chemie. International edition, 2020)
Blink and you'll miss it: A rationally designed small‐molecule label featuring fluorogenic and self‐blinking features has been designed and synthesized for bioorthogonal chemistry and super‐resolutio...
First published: 22 October 2019
Gesehen am 27.02.2020